Prevalence and Associated Factors with Attending Antenatal Care in Akre City, Iraq - Bnar Mustafa Ahmed; Hamdia Mirkhan Ahmed (Hawler Medical University, 2023)
Background and Objectives: Antenatal care is essential for protecting the health of women and their unborn children. Antenatal care utilization is a key intervention in problem detection and treatment, promoting health-seeking behavior, and preparing pregnant women for birth. The present study aimed to investigate the prevalence and associated factors that affect attending and utilizing antenatal care in primary health care centers among pregnant women in Akre city. Methods: A cross-sectional study was conducted in the Maternity Hospital of Akre City from November 21 to February 21, 2022. Data were collected through interviews with 400 women who attended the hospital for delivery and via a questionnaire constructed for the study. The questionnaire included women's socio-demographic characteristics, socio-economic status, obstetrical and reproductive history, and factors affecting antenatal care. Frequency, percentage, and chi-square tests were used to analyze the data. Result: The rate of attending antennal care was 20%. The study findings showed a statistically significant association between attending antenatal care in the last pregnancy with residency, type of family, parity, and previous mode of delivery. Conclusion: The prevalence of women who attend antenatal care is few. Effective media and providing special health care in primary health care centers and services are required to improve the level of awareness of pregnant women for utilizing antenatal care.